Semen parameters and fertility potency of a cloned water buffalo (Bubalus bubalis) bull produced from a semen-derived epithelial cell - Saini, Monika (PLoS One, 2020)
Semen contains epithelial cells that can be cultured in vitro. For somatic cell nuclear transfer applications, it is essential to know whether clone(s) produced from semen-derived epithelial cells (SedECs) are healthy and reproductively competent. In this study, the semen and fertility profile of a cloned bull (C1) that was produced from a SedEC were compared with its donor (D1) and with two cloned bulls (C2, C3) that were produced from commonly used skin-derived fibroblast cells (SkdFCs). We observed variations in some fresh semen parameters (ejaculated volume and mass motility), frozen-thawed sperm parameters (plasma membrane integrity, and computer-assisted semen analysis (CASA) indices), but values are within the normal expected range. There was no difference in sperm concentration of ejaculated semen and frozen-thawed semen parameters which include sperm motility, percentage of live and normal morphology sperm, and distance traveled through oestrus mucus. Following in vitro fertilization (IVF) experiments, zygotes from C1 had higher (P < 0.05) cleavage rates (81%) than C2, C3, and D1 (71%, 67%, and 75%, respectively); however, blastocyst development per cleaved embryo and quality of produced blastocysts did not differ. The conception rate of C1 was 46% (7/15) and C2 was 50% (8/15) following artificial insemination with frozen-thawed semen. Established pregnancies resulted in births of 7 and 6 progenies sired by C1 and C2, respectively, and all calves show no signs of phenotypical abnormalities. These results showed that semen from a cloned bull derived from SedECs is equivalent to semen from its donor bull and bulls cloned from SkdFCs.